Design and development of radiation hard p+n Si pixel detector for the next generation photon science experiment. (2020) - Saini, Nitu; Srivastava, Ajay K.; Kameswara Rao, K.
Abstract: Science, at next generation photon science experiment requires radiation hard p + n Si pixel detector for the X-ray imaging. The choice of an appropriate surface radiation hard X-ray thick Si detector design is a challenging task for the long-term operation of the experiment for the different application that involves up to 25 KeV X-ray energy especially in the material science. The test structure for e.g. prototype p + n Si microstrip detector was fabricated at BEL, Bengaluru, India. The current–voltage and capacitance–voltage characteristic of the detector was measured. The experimental macroscopic parameters are used for the designing of the p + n Si pixel detector. The Visual TCAD semiconductor device simulator from Cogenda was used to compare the simulated and experimental results of the prototype detector to see the electric field distribution in the detector. The breakdown performance of the detector has been discussed using simulation result. The experimentally observed microscopic parameters N fix ox (fixed oxide charge) and Nit (interface trapped charge) can be used in the simulation in order to understand the surface radiation damage performance of the detector. The influences of various device and process parameters on the macroscopic parameters of the detector are shown. In this paper, the influence of the X-ray radiation damage on the electrical performance of the p + n Si pixel detector is shown. On the basis of TCAD simulation and experimental measurement, a radiation-hard p + n silicon pixel sensor design, process, device parameter, and specification is proposed for the next generation photon science experiment like Eu-XFEL.